Комунікативні особливості жінки – керівника закладу освіти. Особливості стилю керівництва - Калінська, Оксана (Видавництво Національного університету "Львівська політехніка", 2009)
Impact of educational establishment female leader communicative peculiarities on her managing activities efficiency.
Keywords: communicative qualities; a communicative nucleus; efficiency of the managing activities